Case report: Novel three-dimensional echocardiographic methods mapping aortic root pseudoaneurysm secondary to blood culture-negative endocarditis with bicuspid aortic valve involvement - Miao, Yue; Zhang, Yanchao; Yue, Ling; Guan, Shuang; Feng, Wei (Frontiers in Cardiovascular Medicine, 2023)
Background Infective endocarditis (IE), though uncommon, is a potentially lethal disease. Blood culture-negative endocarditis (BCNIE) accounts for 2.5%–31% of all cases of IE and can lead to life-threatening complications, including aortic root pseudoaneurysm. It is associated with considerable diagnostic and therapeutic dilemmas. TrueVue and TrueVue Glass include the latest two technologies applied in advanced three-dimensional echocardiography, which allow for novel photorealistic images of cardiac structures, and provide abundant previously unavailable diagnostic information. Herein, based on a series of novel three-dimensional echocardiographic methods, we report a case of BCNIE with aortic valve involvement, leading to aortic valve perforation and prolapse, and developing into a giant aortic root pseudoaneurysm. Case summary In this study, we presented a case of a 64-year-old man exhibiting symptoms of intermittent fever, asthenia, and dyspnea following light exertion. Physical examination, laboratory tests, and electrocardiograms were suspected of IE, though the results of blood cultures were exactly negative. Three-dimensional transthoracic echocardiography, as well as a series of novel advanced techniques, was adopted to clearly visualize the lesions of the aortic valve and aortic root. However, despite active medical treatment modalities, the patient eventually suffered from a sudden, unexpected death 5 days later. Conclusion BCNIE with aortic valve involvement and development into a giant aortic root pseudoaneurysm is a rare and serious clinical event. In addition, TrueVue and TrueVue Glass offer unprecedented photographic stereoscopic images, enhancing the diagnostic performance of such structural heart diseases.